Impact of normalization method on experimental outcome using RT-qPCR in Staphylococcus aureus - Valihrach, Lukas; Demnerova, Katerina (Journal of microbiological methods, 2012)
We performed a gene expression study using RT-qPCR in Staphylococcus aureus. The influence of normalization method was investigated. We confirmed that a recent standard, using more reference genes, was the best normalization strategy. The application of the most commonly used reference genes in 2011 (gyrB and 16S rRNA gene) failed.
Keywords: Reference Standards; bakteriální geny; RNA, Ribosomal, 16S; bakteriální RNA; RNA ribozomální 16S; DNA gyráza; DNA Gyrase; polymerázová řetězová reakce s reverzní transkripcí; Staphylococcus aureus; referenční standardy; Reverse Transcriptase Polymerase Chain Reaction; RNA, Bacterial; exprese genu; transkriptom; Genes, Bacterial; Transcriptome; kvantitativní polymerázová řetězová reakce; Gene Expression; Real-Time Polymerase Chain Reaction